“No One Thinks of Greenland:” US-Greenland Relations and Perceptions of Greenland in the US from the Early Modern Period to the 20th Century - Ingo Heidbrink (American Studies in Scandinavia, 2022)
The history of US-Greenland relations and the perception of Greenland in the US is a near complete historical desideratum with only few works dealing with the subject at all and those publications covering mainly the few well-known historic events. Neither US nor Danish or Greenlandic historians have dealt with the perception of Greenland in the US from Early Modern to today in its entirety.